Penerapan Model Project Based Learning Terintegrasi TPACK untuk Meningkatkan Keaktifan Siswa - Desi Trisnawati; Sutrisna Wibawa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The purpose of this study was to explain: 1) the application of the TPACK integrated Project Based Learning learning model, 2) the results of application the TPACK integrated Project Based Learning learning model have increased student engagement. This study uses a qualitative descriptive approach with field research. Documentation, interviews, and observations are the methods used to obtain data. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of this study indicate that: 1) The TPACK integrated Project Based Learning model can be successfully used in learning Pancasila Education for grade IV at SD Negeri 1 Troso. 2) These indications show that the TPACK integrated Project Based Learning model increases student activeness.